Cyclic and monotonic behaviour of steel-reinforced concrete-filled steel tubular columns. (April 2023) - Ji, Sun-Hang; Wang, Wen-Da; Xian, Wei; Shi, Yan-Li
Abstract: Steel-reinforced concrete-filled steel tubular (SRCFST) column, exhibits high strength and superior fire resistance, is a type of composite members developed by configuring the steel section in conventional concrete-filled steel tubular (CFST) column. In this paper, the cyclic behaviour of SRCFST columns was experimentally investigated. Twenty columns with cross and I-shaped steel sections under cyclic loading were tested. The effects of the axial load ratio and steel section type on the failure modes, lateral load–displacement curves, and seismic performance were investigated. The test results demonstrate that columns with circular cross-sections, which experience severe local buckling and fracture of the steel tube, exhibit superior cyclic performance compared with those with square cross-sections. The steel section type has a negligible influence on the seismic behaviour of the columns. As the axial load ratio increases, the ductility factor and ultimate load of the columns decrease moderately. A finite element (FE) model was developed to investigate the full-range behaviour of the columns under monotonic loading. Finally, design methods were proposed for calculating the lateral capacity of SRCFST columns with circular and square cross-sections. Highlights: Twenty SRCFST columns with different cross-sections under cyclic loading are tested. The seismic performance of SRCFST columns is investigated. Full-range behaviour of SRCFST columns under monotonic loading is analysed. Design methods are proposed for calculating the lateral capacity of SRCFST columns.